Synthesis and applications of [60]fullerene nanoconjugate with 5-aminolevulinic acid and its glycoconjugate as drug delivery vehicles. Issue 11 (22nd February 2022) - Serda, Maciej; Gawecki, Robert; Dulski, Mateusz; Sajewicz, Mieczysław; Talik, Ewa; Szubka, Magdalena; Zubko, Maciej; Malarz, Katarzyna; Mrozek-Wilczkiewicz, Anna; Musioł, Robert
Abstract : The 5-aminolevulinic acid (5-ALA) prodrug is widely used in clinical applications, primarily for skin cancer treatments and to visualize brain tumors in neurosurgery. Abstract : The 5-aminolevulinic acid (5-ALA) prodrug is widely used in clinical applications, primarily for skin cancer treatments and to visualize brain tumors in neurosurgery. Unfortunately, its applications are limited by unfavorable pharmacological properties, especially low lipophilicity; therefore, efficient nanovehicles are needed. For this purpose, we synthesized and characterized two novel water-soluble fullerene nanomaterials containing 5-ALA and d -glucuronic acid components. Their physicochemical properties were investigated using NMR, XPS, ESI mass spectrometry, as well as TEM and SEM techniques. In addition, HPLC and fluorescence measurements were performed to evaluate the biological activity of the fullerene nanomaterials in 5-ALA delivery and photodynamic therapy (PDT); additional detection of selected mRNA targets was carried out using the qRT-PCR methodology. The cellular response to the [60]fullerene conjugates resulted in increased levels of ABCG2 and PEPT-1 genes, as determined by qRT-PCR analysis. Therefore, we designed a combination PDT approach based on two fullerene materials, C60 -ALA and C60 -ALA-GA, along with the ABCG2 inhibitor Ko143.